2016
DOI: 10.1039/c6ra22221h
|View full text |Cite
|
Sign up to set email alerts
|

A simple and efficient in situ generated ruthenium catalyst for chemoselective transfer hydrogenation of nitroarenes: kinetic and mechanistic studies and comparison with iridium systems

Abstract: A convenient and highly efficient in situ generated Ru(ii) system for synthesizing functionalized amines and mechanistic studies and comparison with iridium systems is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 78 publications
0
20
0
Order By: Relevance
“…To shed some light on the mechanism of this tandem transformation, several experiments were carried out. We previously reported that complex 1 followed the direct route in transfer hydrogenation of nitrobenzene to aniline . During the course of this direct transformation of nitroarenes to N ‐methylamines, the corresponding azoarenes or azoxyarenes were not detected, indicating a preference for the direct route .…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…To shed some light on the mechanism of this tandem transformation, several experiments were carried out. We previously reported that complex 1 followed the direct route in transfer hydrogenation of nitrobenzene to aniline . During the course of this direct transformation of nitroarenes to N ‐methylamines, the corresponding azoarenes or azoxyarenes were not detected, indicating a preference for the direct route .…”
Section: Methodsmentioning
confidence: 97%
“…We previously reported that complex 1 followed the directr oute in transfer hydrogenation of nitrobenzenet oa niline. [15] Duringt he course of this direct transformation of nitroarenest oN-methylamines, the corresponding azoareneso ra zoxyarenes weren ot detected, indicating ap reference for the direct route. [21] To further teste this, azobenzene was treated under the optimized conditions, but gave only 5% conversion( Scheme 4a).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…All the commertial reagents and metal precursors were purchased from Sigma‐Aldrich, Alfa‐Aesar, Spectrochem, Avra, SDFCL and Arora Matthey India. The metal complexes were synthesized according to our previous work , . 1 H, 13 C and 31 P NMR spectra were recorded in JEOL Spectrometer.…”
Section: Methodsmentioning
confidence: 99%